Tinjauan Kekuatan Dan Karakteristik Ubin/Tegel Lantai Dengan Menggunakan Agregat Pecahan Genteng - Baskara, Hendra; , Ir. Abdul Rochman, M.T; , Muhammad Ujianto, S.T., M.T (2016)
Tile / tile flooring is one of the building materials used in the construction of a building. These tiles are used instead of the floor plate so that the floor is more comfortable to use and look better. Tiles also many species there are types of ceramics and tiles. In this study will be made tile type floor tiles. This study aims to determine the optimum thick tiles, so that the strength of the tiles from the aggregate tile fragments is the same as ordinary tiles. In this experiment, tile fragments maximum aggregate size of 4.8 mm and the thickness variation of tile 3 cm, 3.5 cm, 4 cm, 4.5 cm, 5 cm. Overview analysis of this study is the compressive strength, flexural strength, shear strength and shear strength in two directions at the age of at least 28 days. Mortar mix design methods using methods SNI 03-6882-2002. After doing research, the thicker the tile density is getting smaller due to the manufacturing process tiles with the smallest thickness under pressure of the press machine is greatest, while the largest thick tiles under pressure is the smallest by press machine. From the calculation of the compressive strength of plain tiles with a thickness of 2.5 cm is 2.7 MPa thick obtained optimum results are almost the same compressive strength is 4.5 cm thick tiles with compressive strength of 2.8 MPa. The results of calculation of bending strength plain tiles with a thickness of 2.5 cm thick is 3,79 MPa obtained optimum results flexural strength is nearly equal that is 3 cm thick tiles firmly insisted 5.31 MPa. The results of calculation of shear strength plain tiles with a thickness of 2.5 cm is 1.31 MPa obtained from the optimum thickness shear strength approaching that is 3 cm thick tiles with the strength that is 2.42 MPa. The result of the calculation of shear strength bidirectional ordinary tiles with a thickness of 2.5 cm is the optimum thickness of 1.00 N is obtained from the results of a two-way shear strength approaching that is 3 cm thick tiles with the strength that is 2.99 N. The optimum thickness of the tiles with tile fragments aggregate is 3 cm to the same strength as ordinary tiles.